ANALYSIS OF BIOLOGY LEARNING IN JUNIOR HIGH SCHOOLS IN THE COVID-19 ERA - Cartono Cartono (Sean Institute, 2023)
In 2020, the learning process in Indonesia was disrupted due to the Covid-19 outbreak. The Indonesian Ministry of Education and Culture has changed techniques for online-based learning activities, including biology education. This research aims to determine the problems of biology education in junior high schools in the era of the Covid-19 pandemic. This research is descriptive qualitative research. The subjects used in this research were students and teachers. The object of this research is to analyze the problems of students and teachers in carrying out learning in junior high schools in the era of the Covid-19 pandemic. The research results show that the implementation of biology learning during the COVID-19 pandemic, especially in online format, faces a number of challenges that affect the effectiveness of the teaching and learning process. Internet network problems, especially in rural areas, are a serious obstacle, resulting in difficulties for students' access to platforms such as WhatsApp, Zoom Meeting, Google Classroom, and Google Meeting. The difficulty in understanding biological concepts by students emphasizes the need for a more in-depth learning approach and an increase in the role of teachers in providing detailed explanations. Limited infrastructure and technological accessibility illustrate inequalities in online learning. Therefore, collaborative initiatives are needed between the government, schools, teachers and students to overcome technical obstacles and improve the quality of biology learning during the pandemic.